1990
DOI: 10.1007/bf01313151
|View full text |Cite
|
Sign up to set email alerts
|

Post-bloom grazing byCalanus glacialis, C. finmarchicus andC. hyperboreus in the region of the Polar Front, Barents Sea

Abstract: The plankton community in the Polar Front area of the Barents Sea was investigated during a cruise from 14 to 28July 1987. The colonial algae Phaeocystis pouchetii and Dinobryon pellucidum dominated the phytoplankton. Depth integrated carbon assimilation rates varied from 190 to 810 mg C m -2 d-1. A high carbon:chlorophyll ratio (which varied from 123 to 352) prevailed at the three stations investigated, which may relate to facultative heterotrophic behaviour by D. pellucidum. The herbivorous zooplankton commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…As previously noted, our experimental estimates of gut clearance rates, derived mainly from copepods, are in good agreement with the temperature-dependent trends from other studies (Dam & Peterson 1988). Among the organisms sufficiently numerous to be included in our experiments, we found no substantial differences in gut clearance rates among species, sizes, or developmental stages (see also Tande & Bdmstedt 1985, Hansen et al 1990, Morales et al 1990, Peterson et al 1990). Penry & Frost (1990) warned that the general approach to estim a t~n g gut clearance rates from the decrease in gut pigments of animals in filtered seawater may lead to significant over-or underestimates of true turnover times.…”
Section: Grazing Rate Estimatessupporting
confidence: 80%
“…As previously noted, our experimental estimates of gut clearance rates, derived mainly from copepods, are in good agreement with the temperature-dependent trends from other studies (Dam & Peterson 1988). Among the organisms sufficiently numerous to be included in our experiments, we found no substantial differences in gut clearance rates among species, sizes, or developmental stages (see also Tande & Bdmstedt 1985, Hansen et al 1990, Morales et al 1990, Peterson et al 1990). Penry & Frost (1990) warned that the general approach to estim a t~n g gut clearance rates from the decrease in gut pigments of animals in filtered seawater may lead to significant over-or underestimates of true turnover times.…”
Section: Grazing Rate Estimatessupporting
confidence: 80%
“…Hansen et al (1990) noted that Calanus spp. displayed no consistent day-night vertical migration patterns during springsummer seasons.…”
Section: Discussionmentioning
confidence: 99%
“…High zooplankton abundance often coincides spatially with high chl a concentration (Hansen et al 1990), and food concentration may stimulate diel migratory behaviour (Conover 1988, and citations therein). Herman (1983) observed that peaks of Calanus glacialis and C. finmarchicus occurrence in north-eastern Baffin Bay were commonly situated 3 to 4 m above the chl a maximum, whereas the distribution pattern of C. hyperboreus coincided with the chl a peak.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, however, have shown that high latitude zooplankton can consume a large portion of phytoplankton production (e.g. Hansen et al 1990, Nielsen & Hansen 1995. This variability might reflect seasonal and regional shifts in the ratio between grazers and primary production (Landry et al 1994a).…”
Section: Impact Of the Zooplankton Community On The Bloommentioning
confidence: 99%